2015
DOI: 10.1021/acs.est.5b02258
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Energy Performance of an Advanced, Aqueous Ammonia-Based CO2 Capture Technology for a 500 MW Coal-Fired Power Station

Abstract: Using a rate-based model, we assessed the technical feasibility and energy performance of an advanced aqueous-ammonia-based postcombustion capture process integrated with a coal-fired power station. The capture process consists of three identical process trains in parallel, each containing a CO2 capture unit, an NH3 recycling unit, a water separation unit, and a CO2 compressor. A sensitivity study of important parameters, such as NH3 concentration, lean CO2 loading, and stripper pressure, was performed to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 25 publications
1
49
0
Order By: Relevance
“…The cold rich stream was split to recover the energy contained in the upcoming high temperature water vapor; meanwhile the rich solvent was heated to release part of the CO 2 . This process has proven to be effective in process simulations as well as in the Tarong pilot plant trials . In this study, the unsplit stream was introduced at the stage 5 (20 stages in total) after crossing the heat exchanger while the split stream was fed to the top of the stripper.…”
Section: Process Improvement Of Mea‐based Co2 Capture Processmentioning
confidence: 99%
“…The cold rich stream was split to recover the energy contained in the upcoming high temperature water vapor; meanwhile the rich solvent was heated to release part of the CO 2 . This process has proven to be effective in process simulations as well as in the Tarong pilot plant trials . In this study, the unsplit stream was introduced at the stage 5 (20 stages in total) after crossing the heat exchanger while the split stream was fed to the top of the stripper.…”
Section: Process Improvement Of Mea‐based Co2 Capture Processmentioning
confidence: 99%
“…Compared to the benchmark absorbent − MEA, ammonia has several advantages, such as a lower heat requirement for CO 2 desorption, no absorbent degradation, low absorbent cost, and capacity for simultaneous removal of CO 2 and SO 2 from flue gas. Therefore, aqueous ammonia solution (AA) can be used as an alternative absorbent for CO 2 capture from flue gas, and research on pilot plants has been carried out . Ammonia is also an essential feedstock for chemical engineering and fertilizer for crop production.…”
Section: Inorganic Renewable Absorbentsmentioning
confidence: 99%
“…Subsequently, this change will affect the absorption equilibrium in the absorber and eventually the rich loading. Li et al . have optimized the rich‐split fraction for aqueous ammonia PCC pilot‐plant trials and reported that, at 5% rich‐split fraction, the regeneration duty can be reduced from 3.27 to 2.89 MJ / kg CO 2 and the condensate duty dropped from 1.45 to 0.39 MJ / kg CO 2.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This reduction includes 11.6% in the reboiler duty and 73.1% for the condenser. According to Li et al ., increasing the rich‐split fraction will substantially reduce the heat of vaporization and subsequently the condenser duty, but would also noticeably increase the sensible heat and the reboiler duty. For example, at a 10% rich‐split fraction, the reboiler duty was even higher than the conventional reboiler duty by 1.8%, while the condenser duty was substantially reduced by 94.4%.…”
Section: Model Descriptionmentioning
confidence: 99%